Electrodeposited MoOx films as negative electrode materials for redox supercapacitors - Upadhyay, Kush (2017)
MoOx films composed of agglomerated nanoparticles were synthesized by potentiostatic electrodeposi-tion on stainless steel collectors for charge storage electrodes working in aqueous electrolyte (1 M H2SO4) and negative potential window. The agglomerated nanoparticles were amorphous in nature and possess mixed valance state. By optimizing the charge density applied during electrodeposition, the electrodes delivered maximum specific capacity of 228 C g_1 (507 F g_1) at 1 A g_1 for the sample electrodeposited at _0.3 C cm_2. This film showed very good rate capability and retained around 48% of specific capacity at 10 A g_1. The galvanostatic charge discharge cycling stability test showed 87% of initial capacity retained after 900 cycles, suggesting good stability behaviour. Electrochemical impedance spectroscopy (EIS) measurements evidenced lower equivalent series resistance for the sample electrodeposited at _0.3 C cm_2 among the tested samples, revealing its better electrochemical performance. Aging of the electrode with higher specific capacity was also investigated by performing EIS after different cycles; the results revealed an increment on the overall resistance, thus clarifying the capacity degradation.